3D macroscopic graphene oxide/MXene architectures for multifunctional water purification. (15th October 2020) - Ming, Xin; Guo, Ankang; Zhang, Qian; Guo, Zhenzhen; Yu, Fang; Hou, Baofei; Wang, Yu; Homewood, Kevin Peter; Wang, Xianbao
Abstract: Solar-driven interfacial evaporation is an efficient and economical technology for converting low-grade solar energy to high-grade steam energy. However, solar water evaporators that exhibit both high water vapor generation ability and multifunction water purification are still less reported. Herein, the 2D Ti3 C2 Tx (MXene) is tactfully assembled into 3D porous macroscopic aerogel monoliths by a graphene oxide (GO)-assisted process as an independent solar-driven interfacial evaporator for efficient and all-around water purification. GO is weakly reduced by MXene to reduced graphene oxide (RGO) during the process, leading to a self-enhanced photothermal conversion regulation. The floating GO/MXene aerogel (GMA)-based evaporator achieves high solar evaporation efficiency up to 90.7% with an evaporation rate of 1.27 kg/m 2  h under one sun irradiation. Several simple prototypes have been designed and implemented as demonstrators of practical water purification in both summer and winter. The portable GMA could realize all-around water purification for rapid and effective elimination of salting, organic pollutants, bacterium and other contaminants as a personalized water purification system. Graphical abstract: A 3D macroscopic architecture of MXene-based system with a synergistically self-enhanced photothermal conversion process was fabricated to serve as a novel and efficient solar-driven interfacial evaporator with high evaporation efficiency of 90.7% under 1 kW/m 2 light irradiation, which could also realize all-around and stable water purification in real life. Image 1 Highlights: 3D GO/Mxene architectures were assembled for multifunctional water purification. Their solar evaporation efficiency up to ∼90.7% with an evaporation rate of 1.27 kg/m 2  h. The superior performances due to the synergistically self-enhanced photothermal conversion. Multifunctional water purification of removing inorganic ions, organic dyes, bacterium. Several portable water purification prototypes for practical applications in real life.